A linguagem jornalística como representação da mulher na sociedade - Lain, Regina de Fátima (My University, 2019)
The present work is dedicated to the analysis of the journalistic language employed in news stories related to women. The theoretical basis of this study is found in the study of language itself and the formation of journalistic language, the history and role of women in society and the relationship between language and the construction of the concept of women in society. The sample provided for the analysis consists in ten distinct news pieces, divided into four categories:women in focus (seasonal motive), a map of violence, women in the spotlight (personal approach), and women as source of information. The methodological strategy is based on Knowledge Mapping, an approach proposed by Baptista (2012), which involves personal input, literature review and the identification and collection of materials and analysis of texts found in the news pieces. After the study, it was found that, regardless of the category, journalistic language showed brief signs of improvement in relation to approaches in older news stories about women, especially in respect to the agendas set; however, the discourse employed still carries veiled biases and stereotyped characterizations of the feminine (sic).
Este trabalho dedicou-se a analisar a linguagem jornalística em matérias relacionadas à mulher. A base teórica deste estudo é composta pelo estudo da linguagem em si e da formação da linguagem jornalística, a história e o papel da mulher na sociedade e a relação entre a linguagem e a construção da mulher na sociedade. Nesta monografia é realizada uma análise com base em uma amostragem de dez matérias distintas, divididas em quatro categorias: mulher em foco, mapa da violência, em destaque e mulher e informação. A estratégica metodológica baseia-se na Cartografia dos Saberes, proposta por Baptista (2012), e envolve a produção de conteúdos originais, o levantamento bibliográfico, a identificação e coleta dos materiais e a análise dos textos encontrados. Após o estudo, verificou-se que, independentemente da categoria, a linguagem jornalística mostrou breves sinais de melhora em relação a abordagens antigas de matérias sobre mulheres, principalmente no que diz respeito às pautas produzidas; no entanto, o discurso ainda traz um preconceito velado e caracterizações estereotipadas do feminino (sic).
Keywords: Jornalismo; Redação de textos jornalísticos; Mulheres